KULTURNO PAMĆENJE KAO KULTURNI IZAZOV (Philological Studies, 2019)
This paper deals with the concept of culture, in general, and cultural identity, as a fluid and complex discourse, and not just as an abstract idea, but much alive, unavoidable antrophological and social phenomena. As a result of this, the existence and knowledge of cultural identities reflects essential human needs. The cultural identity paradigm changes with time, varying according to the geography of place, as well as the social dominators which create it. It includes cultural modification such as the end of utopia, massmedia society, global capitalism, postindustrial society, microtechnology, feminism, ecology. It is marked by the end of the meta-stories and totalitarity, enabling at the same time the creation of small stories, as, for example, the urge of small nations to be free. The new cultural postmodern code is dialogical, with plural paradigms as it replaces the monological one, that of modern culture. This new orientation is of particular importance to small, marginalized nations, as those from South-Eastern Europe, or the West Balkans, that refract all the dimension of the recent present.
Keywords: culture, cultural identity, insecure poliphonic subject, the end of metastories, the identity of small nations